Perceptions of unwanted sexual behaviour on public transport: exploring transport density and behaviour severity - Ball, Krista S. (Crime prevention and community safety, 2017)
This study focuses on bystander perceptions and expected responses to unwanted sexual behaviours on public transport. Level of blame, incident seriousness, likelihood of reporting and intervening were evaluated using a series of 6 vignettes that manipulated passenger density and severity of the behaviour. Half of the participants also viewed a video to raise their awareness of unwanted sexual behaviours. The results indicated that blame was attributed to the perpetrator and not the victim, with perpetrator blame, incident seriousness and likelihood of reporting all being influenced by a passenger density and behaviour severity interaction. Increasing awareness of unwanted sexual behaviours had no effect with the exception of likelihood of intervention. Findings are discussed in relation to women’s safety during travel in peak and off peak hours as well as the role of the bystander. Finally, the article concludes with considerations of these findings for women’s safety in transit settings.